Senegalin-2: A Novel Hexadecapeptide from Kassina senegalensis with Antibacterial and Muscle Relaxant Activities, and Its Derivative Senegalin-2BK as a Bradykinin Antagonist - Yueyang Lu; Yanguo Zhu; Chengbang Ma; Lei Wang; Mei Zhou; Tianbao Chen; Xiaonan Ma; Xu Zhang; Zhimin Fan (Biomolecules)
The amphibian skin secretions are excellent sources of bioactive peptides, some of which and their derivatives exhibit multiple properties, including antibacterial and antagonism against bradykinin. A novel peptide Senegalin-2 was isolated from the skin secretions of Kassina senegalensis frog. Senegalin-2 relaxed rat bladder smooth muscle (EC50 17.94 nM) and ileum smooth muscle (EC50 135 nM), inhibited S. aureus and MRSA at 2 μM, and exhibited low hemolytic activity with no cytotoxicity. To design effective bradykinin antagonists, Senegalin-2 was conjugated with bradykinin to synthesize Senegalin-2BK. This modification retained potent activity against Gram-positive bacteria. Compared to Senegalin-2, Senegalin-2BK significantly reduced hemolysis and exhibited a more than threefold increase in the selectivity index. Furthermore, Senegalin-2BK contracted the bladder (EC50 2.83 μM) and ileum (EC50 56.64 nM)’s smooth muscle. The pretreatment with 10−7 M Senegalin-2BK reduced the 10−6 M bradykinin contraction on the bladder by over 70%. In conclusion, Senegalin-2 has dual functionalities as an antibacterial agent and muscle relaxant, positioning it as a potential therapeutic candidate for managing overactive bladder. As a synthetically derived bradykinin antagonist and myotropic peptide with antibacterial properties, Senegalin-2BK shows promise in effective therapies for relieving pain, inflammation, and addressing muscular disorders such as urinary retention, constipation, and infections.